2020
DOI: 10.1039/d0fo01105c
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed oligosaccharides alleviate DSS-induced colitis through modulation of gut microbiota and repair of the intestinal barrier in mice

Abstract: Intestinal epithelial barrier dysfunction with dysbiosis of gut microbiota contributes to the occurrence and acceleration of colitis. This study aimed to evaluate the effect of flaxseed oligosaccharides (FOS) on dextran...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 58 publications
5
36
0
1
Order By: Relevance
“…During the last twenty years, multiple publications identified a changed composition and metabolism of the gut microbiota associated with increased SCFA concentrations as a possible anti-inflammatory mechanism [ 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ]. In contrast, high-sugar diet was shown to enhance susceptibility to DSS-colitis via depletion of luminal short chain fatty acids [ 181 ].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…During the last twenty years, multiple publications identified a changed composition and metabolism of the gut microbiota associated with increased SCFA concentrations as a possible anti-inflammatory mechanism [ 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ]. In contrast, high-sugar diet was shown to enhance susceptibility to DSS-colitis via depletion of luminal short chain fatty acids [ 181 ].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…Many of them (e.g., Flavonifractor , Enterorhabdus , Desulfovibrio , Elusimicrobium , Roseburia , Candidatus _ Saccharimonas , Anaerovorax , Caproiciproducens , Lachnoclostridium , Ruminiclostridium , Intestinimonas ) play a key role in immunity regulation and intestinal health ( Zhang et al, 2020a ; Zhang et al, 2020b ; Zhao, Jiang & Chu, 2020 ; Ward et al, 2017 ; Zhang et al, 2020a ; Zhang et al, 2020b ). However, Unidentified_Clostridiales , Oscillibacter , Anaerofilum , Parasutterella , Tyzzerella , Blautia , Peptococcus , Mycoplasma , Helicobacter , Butyricimonas have pathogenic and pro-inflammatory effects ( Xu et al, 2020 ; Xue et al, 2020 ; Xie et al, 2020 ). The change in their abundance of these bacteria with age may be a potential reason for the shorter life span (around one year) of Brandt’s voles in the wild.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested the signatures of micriobial composition and metabolites might be used to predict the action mechanisms of prebiotic or probiotic. 24,[35][36][37][38] The presenting results suggested that FOS supplementation might prevent the DSS-induced dysbiosis of gut microbiota, by increasing the abundance of potentially beneficial bacteria (e.g., Faecalibaculum and Bifidobacterium) and decreasing the abundance of potentially harmful bacteria (e.g., Mucispirillum), but the mechanisms need to be further explored.…”
Section: The Modulation Of Gut Microbiota By Fos Supplementation In Acute Colitis Micementioning
confidence: 95%